2021
DOI: 10.2147/idr.s331434
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicine Practice in the Context of COVID-19 Pandemic: Community Claim in Jimma Zone, Oromia, Ethiopia

Abstract: Purpose: To assess traditional medicine practice claims by the community for the prevention and treatment of COVID-19. Methods: A community-based cross-sectional study design was conducted among 422 households of Jimma Zone, and the data were collected by interviewing individuals from the selected households. The medicinal plants were recorded on Microsoft excel 2010 with their parts used, dosage form, route of administration and source of plants and tabulated in the table. Descriptive statistics were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
1
19
0
2
Order By: Relevance
“…Stephania glabra, Woodfordia fruticosa, Betula utilis, Nelumbo nucifera , and Calotropis gigantean have been identified as effective antimicrobial plants (in vitro) [ 6 ]. Recently, some medicinal plants have been reported to possibly possess anti-SARS-CoV-2 activity (in vitro), such as Lycoris radiate, Artemisia annua, Pyrrosia lingua, Nigella sativa , and Houttuynia cordata [ 7 ]. It is important to mention that clinical trials are required to demonstrate all these possible activities, particularly regarding SARS-CoV-2, for which no effective drug based on natural products has been approved yet.…”
Section: Introductionmentioning
confidence: 99%
“…Stephania glabra, Woodfordia fruticosa, Betula utilis, Nelumbo nucifera , and Calotropis gigantean have been identified as effective antimicrobial plants (in vitro) [ 6 ]. Recently, some medicinal plants have been reported to possibly possess anti-SARS-CoV-2 activity (in vitro), such as Lycoris radiate, Artemisia annua, Pyrrosia lingua, Nigella sativa , and Houttuynia cordata [ 7 ]. It is important to mention that clinical trials are required to demonstrate all these possible activities, particularly regarding SARS-CoV-2, for which no effective drug based on natural products has been approved yet.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 5 , 6 , 9 , 12 , 17 , 19 , [23] , [24] , [25] , 28 , 37 , [39] , [40] , [41] , 51 , 52 , 56 , 64 , 68 , 70 , 72 , 73 , 75 , 79 , 80 , [85] , [86] , [87] ]…”
Section: Uncited Referencesunclassified
“…ex Benth.) Umeta Chali et al [ 110 ] Peru 17 (used in the treatment of respiratory symptoms during the COVID-19 pandemic Eucalyptus globulus Labill. , Piper aduncum L. , Zingiber officinale Roscoe , Allium sativum L. , Matricaria recutita L Villena-Tejada et al [ 115 ] Cameroon 29 Citrus aurantiifolia (Christm.)…”
Section: Main Textmentioning
confidence: 99%
“…As reported in Table 2 , in Ethiopia, 32 herbal and non-herbal medicinal products and 15 plant species have been used in African traditional medicine to treat and prevent symptoms of COVID-19 [ 110 ]. In another study, a total of 111 plant species have been identified which are used to treat viral infections by the traditional healers of Ethiopia and are suggested as potential therapeutics against COVID-19 [ 103 ].…”
Section: Main Textmentioning
confidence: 99%